Analisis Faktor Pendukung dan Penghambat Pariwisata dalam Mempengaruhi Kondisi Sosial Ekonomi Masyarakat di Kecamatan Kabila Bone, Kabupaten Bone Bolango, Provinsi Gorontalo - Ibrahim, Yuniarti; Maryati, Sri; Pratama, M.Iqbal Liayong (-, 2024)
Kabila Bone sub-district has great tourism potential, but its development is still hampered by several factors, such as limited infrastructure, low human resource capacity, and challenges in preserving local culture. Although the tourism sector in this area can have a positive impact on the local economy, these constraints prevent the maximum utilisation of existing tourism potential. This study aims to analyse the supporting and inhibiting factors in the development of the tourism sector in Kabila Bone sub-district, as well as to evaluate its impact on the socioeconomic conditions of the local community. This research uses a descriptive qualitative approach with purposive sampling technique for selecting research subjects. Data were collected through interviews, documentation, and field observations, while data analysis was conducted using an interactive model, which includes data collection, reduction, and presentation. The results show that the main supporting factors in tourism development are supportive government policies and active community participation, while the inhibiting factors are limited infrastructure and lack of human resource training. The impact of tourism on the socio-economy of the community in Kabila Bone Sub-district can increase income, create business opportunities, and help preserve local culture, but if not managed properly, this sector has the potential to damage the environment. Based on the results of the study, it can be concluded that the development of the tourism sector has a positive impact on the socio-economic welfare of the community, but to maximise tourism potential, challenges related to infrastructure and human resource capacity need to be addressed.